(untitled) (Journal of actual problems of jurisprudence, 2018)
The article deals with the problem of international projects aimed at the development of quality assurance in engineering education in Central-Asia. European Union project aimed at introducing effective regional education management system always occupy an important place in the development of the region as well as the individual countries. Despite this, not all initiatives can be realized completely, as in the region there is no single harmonized policy on quality assurance and qualification recognition system, respectively. Comprehensive, effective, legal solution to these issues will effectively integrate the region into the world educational space. Key words: engineering education, public-legal regulation, certification, accreditation.